Memiliki Perlindungan Lingkungan Hidup Melalui Analisis Daya Tampung Beban Pencemaran Sungai Kedurus Kecamatan Wiyung Surabaya - Taufiqurrahman, Ahmad; Nurmaningsih, Dyah Ratri; Pribadi, Arqowi (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2023)
Kedurus river is located in a residential and agricultural area in the Wayang sub-district, Surabaya. Domestic and non-domestic activities around the river have provided excessive pollutants to the river, more than the standard contents as regulated by the government. This study is aimed to measure the pollution level in the river. Regulation PP 22 of 2021 is used as a quality standard while the capacity to accommodate pollution loads is calculated based on Kempten-LH No. 110 of 2003. Based on the research results, the DO, TDS, BOD, COD, and Ammonia parameters at points 1, 2, and 3, and the TSS and detergent parameters at point 3 indicated concerns for the quality of the water environment. This can be seen from the measurement values that exceed the pollution load capacity limit in accordance with class II quality standards, Government Regulation No. 22 of 2021. Appropriate measures are needed to improve the condition of the water environment to protect the health and survival of the living things in the river and maintaining the sustainability of aquatic ecosystems.Keywords – Pollution Load Capacity, Kedurus River,